O Greenblattovih interpretacijah razmerja med Prosperom in Kalibanom - Kernev-Štrajn, Jelka (Primerjalna književnost, 2001)
Greenblatt's interpretations of the relationship between Prospero and Caliban. - The paper presents some of the main methodological features of new historicism. It briefly outlines the history of the beginnings of this phenomenon and its characteristics. It focuses on Greenblatt's work, particularly on his interpretations of the relationship between Prospero and Caliban in Shakespeare's play The Tempest. On the basis of this the paper comes to the conclusion that some of Greenblatt's texts from the 1980s were subject to a colonial discourse that he himself had beforehand found out to be inappropriate for the interpretation of The Tempest.
Keywords: Greenblatt, Stephen; literarna veda; literary science; interpretacije; novi historizem; književnost; literature